2016
DOI: 10.1007/s00190-016-0974-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-rapid earth rotation determination with VLBI during CONT11 and CONT14

Abstract: We present earth rotation results from the ultrarapid operations during the continuous VLBI campaigns CONT11 and CONT14. The baseline Onsala-Tsukuba, i.e., using two out of the 13 and 17 stations contributing to CONT11 and CONT14, respectively, was used to derive UT1-UTC in ultra-rapid mode during the ongoing campaigns. The latency between a new observation and a new UT1-UTC result was less than 10 min for more than 95% of the observations. The accuracy of the derived ultra-rapid UT1-UTC results is approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Using a European and a global GPS network, including three of the GPS stations used in this study, Meindl et al (2004) showed that the north gradient has a clear dependence on latitude when averaged over long timescales. For the area of interest in this study, we specifically mention the Icelandic low-pressure system that typically evolves in the winter and disappears in the summer (Hewson and Longley, 1944). This is a component in the North Atlantic Oscillation and the Arctic Oscillation (Thompson and Wallace, 1998;Sanchez-Franks et al, 2016).…”
Section: Cause Of Horizontal Gradients and Modelsmentioning
confidence: 99%
“…Using a European and a global GPS network, including three of the GPS stations used in this study, Meindl et al (2004) showed that the north gradient has a clear dependence on latitude when averaged over long timescales. For the area of interest in this study, we specifically mention the Icelandic low-pressure system that typically evolves in the winter and disappears in the summer (Hewson and Longley, 1944). This is a component in the North Atlantic Oscillation and the Arctic Oscillation (Thompson and Wallace, 1998;Sanchez-Franks et al, 2016).…”
Section: Cause Of Horizontal Gradients and Modelsmentioning
confidence: 99%
“…This supremacy of the baseline with Hobart is in fact beneficial for the SI program in view of a routine operation that should provide rapid service UT1−UTC. The general concept of e-VLBI and ultra-rapid operations for Earth rotation determination is described in Sekido et al (2008) and Haas et al (2017). Since the station Yarragadee does not facilitate e-transfer of the observation data, UT1− UTC cannot be delivered rapidly from the full SI baseline configuration.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The CONT08 observations were processed by OCCAM and the stronger diurnal ERP signals in summer were detected (Sun et al 2010). The ultra-rapid Earth rotation results were obtained by processing the CONT11 and CONT14 observations, and the results showed that the CONT results agree with IERS 08 C04 in terms of standard deviation during CONT11 on the level of 16-22 µs, but for CONT14 on the level of 9-12 µs (Haas et al 2016). The model of the diurnal and semidiurnal variations in ERP due to lunisolar tides in the world ocean influenced the ERP estimation of the VLBI experiment (Gubanov et al 2015).…”
Section: Introductionmentioning
confidence: 97%